Ungrateful mammals - Eggers, Dave (Abrams, 2017)
Before he embarked on his writing career, Dave Eggers was classically trained as a draftsman and painter. He then spent many years as a professional illustrator and graphic designer before turning to writing full-time. More recently, in order to raise money for ScholarMatch, his college-access nonprofit, he returned to visual art, and the results have been exhibited in galleries and museums around the country. Usually involving the pairing of an animal with humorous or Biblical text, the results are wry, oddly anthropomorphic tableaus that create a very entertaining and eccentric body of work from one of today's leading culture makers.